Influence Mastery ICT And ICT Facilities on the Performance of Employees of the PUPR Department of Minahasa District - Rombon, Daudson EA; Rompas, Parabelem T. D.; Oroh, Rolly R (International Journal of Information Technology and Education, 2024)
Study This aim study influences mastery of Technology Information and Communication (ICT) and means ICT infrastructure towards performance employees at the Department of Employment Regency Public and Public Housing (PUPR) Minahasa. Study This uses a quantitative method with an approach survey involving 30 PUPR Service employees as respondents. Data is collected through a questionnaire tested for validity and reliability. Data analysis was carried out using multiple linear regression to influence independent to dependent variables. Research results show that ICT mastery has a positive and significant effect on the performance of employees. Likewise, ICT infrastructure also has a positive and significant impact on the performance of employees. This matter indicated that the more ICT mastery and more good means available for ICT infrastructure, the performance of Regency PUPR Service employees Minahasa will the more increase. Findings This emphasized the importance of improving ICT capacity and provision means adequate infrastructure for support optimization performance employee. Conclusion of the study This is that mastery of ICT and facilities ICT infrastructure is a factor crucial in increasing the performance of employees. Therefore, it is recommended that the government keep increasing training and development of ICT skills for employees as well as ensure availability means adequate infrastructure use support duties and functions. This Study's expectation can contribute to the planning and retrieval of more policies effective for the public, especially in field infrastructure and services in the District Minahasa.